(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Generation Z exhibits unique learning characteristics, such as reliance on technology, a preference for interactive learning, and active engagement in the learning process. This study aims to identify effective strategies to enhance teacher professionalism in bridging the gap between traditional teaching methods and the needs of Generation Z. The study employs a qualitative descriptive method based on a literature review. Data were collected through the identification, selection, and in-depth analysis of 11 relevant scholarly articles. Content analysis techniques were used to categorize the data into main themes, such as digital literacy gaps, unequal technological infrastructure, resistances to change, and a lack of continuous professional training. The findings reveal that the primary challenges faced include digital literacy gaps, unequal technological infrastructure, resistance to change, and insufficient continuous training. Recommended solutions include implementing digital literacy training, developing innovative curricula such as gamification and flipped classrooms, improving technological infrastructure, and strengthening supervision by school principals. Furthermore, teachers are encouraged to collaborate through professional learning communities to share experiences and teaching strategies